Swedish high school students' knowledge and attitudes regarding fertility and family building - Ekelin Maria; Åkesson Cecilia; Ångerud Malin; Kvist Linda J (BMC, 2012)
Abstract Background Infertility is a serious problem for those who suffer. Some of the risks for infertility are preventable and the individual should therefore have knowledge of them. The purposes of this study were to investigate high-school students' knowledge about fertility, plans for family building and to compare views and knowledge between female and male students. Methods A questionnaire containing 34 items was answered by 274 students. Answers from male and female students were compared using student's t-test for normally distributed variables and Mann-Whitney U-test for non-normal distributions. The chi-square test was used to compare proportions of male and female students who answered questions on nominal and ordinal scales. Differences were considered as statistically significant at a p-value of 0.05. Results Analyses showed that 234 (85%) intended to have children. Female students felt parenthood to be significantly more important than male students: p = <0.01. The mean age at which the respondents thought they would like to start to build their family was 26 (± 2.9) years. Men believed that women's fertility declined significantly later than women did: p = <0.01. Women answered that 30.7% couples were involuntarily infertile and men answered 22.5%: p = <0.01. Females thought it significantly more likely that they would consider IVF or adoption than men, p = 0.01. Men felt they were more likely to abstain from having children than women: p = <0.01. Women believed that body weight influenced fertility significantly more often than men: p = <0.01 and men believed significantly more often that smoking influenced fertility: p = 0.03. Both female and male students answered that they would like to have more knowledge about the area of fertility. Conclusions Young people plan to start their families when the woman's fertility is already in decline. Improving young people's knowledge about these issues would give them more opportunity to take responsibility for their sexual health and to take an active role in shaping political change to improve conditions for earlier parenthood.